Dr. Mohammed Asaduzzaman on agriculture and climate change in Bangladesh - Asaduzzaman, Mohammed (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Climate change has become a major component of government plans for dealing with food security as nations see unprecedented changes in growing conditions. How are climate change concerns influencing agriculture policies in Bangladesh?